Creativity: Flow and the Psychology of Discovery and Invention - Mihaly Csikszentmihalyi (Harper Perennial, 1997)
This book is about what makes life worth living. The creative excitement of the artist at her easel or the scientist in the lab comes as close to the ideal fulfillment as we all hope to, and so rarely do. Professor Mihaly Csikszentmihalyi interviewed more than ninety of possibly the most interesting people in the world - people like actor Ed Asner, authors Robertson Davies and Nadine Gordimer, scientists Jonas Salk